Semi-Generalized Closed Mappings and Generalized-Semi Closed Mappings and Its Relationships with Semi-Normal and Semi-Regular Spaces - Salman, Zahra Ismaeel (Al-Nahrain Journal of Science, 2018)
In this paper, the semi-generalized closed maps (sg-closed maps) and generalized semi-closed maps (gs-closed maps) are studied and some results are presented and proved including the study of some of their basic properties which are related to such type of mappings. Also, a study of s-normal spaces and s-regular spaces is given using its relationships with sg-closed and gs-closed mappings.